The mental health of health workers due to the effect of the pandemic in Latin America - García Godos Peñaloza, Carla Soledad (2023)
The study is part of the effects of the pandemic in the context of Covid-19 on the mental health of the health teams that directly faced this scourge. The objective of the research is to review the influence on the mental health of the worker and the measures taken to mitigate its effects in Latin America. The materials and method were made through documentary analysis from a filter by authors, and keywords in English and Spanish; A sample of 28 articles from Web of Science, Scopus and the Google Scholar search engine was obtained between 2020 and 2022. Results: depression and distress 9 articles; Anxiety 8; Insomnia 5; distress 4; intolerance, fatigue and Bournot syndrome 2; uncertainty and suicidal ideation 1. In addition, there was a work overload in health workers leading to a saturation in their activities, producing harmful effects on their mental health; scarcity of materials led to facing the pandemic without the necessary conditions, causing fear of contagion in their families; women were the most affected by the feeling towards home, leading them to critical situations.